Multilevel latent class modeling to segment the microfinance market. Issue 5 (12th February 2019) - Souza, Lucas Lopes Ferreira; Bassi, Francesca; Ferreira de Freitas, Ana Augusta
Abstract : Purpose: Microfinance has become an important way to alleviate poverty. Though four decades have passed since its introduction, its impact is still not entirely clear. What makes it difficult to ascertain its efficacy is the existence of diverse types of microfinance organizations and client profiles. Microfinance institutions must primarily pay more attention to the client, and to the mechanism through which financial services are delivered. The purpose of this paper is to identify the profiles of microfinance customers and the features of their operations. Design/methodology/approach: In this paper, multilevel latent class models were estimated to reveal clusters of operations and classes of clients. Findings: The results show that there are six clusters of operations and four classes of clients in the market, each with distinct profiles and needs. Different strategies are recommended for each cluster and class. Originality/value: Numerous studies have focused on the importance of getting to know the clients of microfinance programs, but none as yet have used market segmentation as a way to do so. The goal is to generate better strategies to help clients improve their business results. Applying market segmentation to the microfinance market may point to different products for different groups of clients, taking the real needs of each of them into account.